2002
DOI: 10.1002/biof.5520160104
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin differentially regulates TGF‐β1, its receptors and nitric oxide synthase during impaired wound healing

Abstract: Wound healing is a highly ordered process, requiring complex and coordinated interactions involving peptide growth factors of which transforming growth factor-beta (TGF-beta) is one of the most important. Nitric oxide is also an important factor in healing and its production is regulated by inducible nitric oxide synthase (iNOS). We have earlier shown that curcumin (diferuloylmethane), a natural product obtained from the plant Curcuma longa, enhances cutaneous wound healing in normal and diabetic rats. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
92
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 30 publications
(51 reference statements)
6
92
0
1
Order By: Relevance
“…An interesting finding was observed in samples of turmeric group and marigold group at day 7 (D7), where newly formed keratinized layer of epidermis along with newly formed connective tissue was found under the scab infiltrated with reactive cells (Figure 6a, 6b). Curcumin may be useful in conditions of impaired wound healing, as it appears to induce endogenous production of TGF-β1 in the wound which can play an important role in improvement of wound repair (Mani et al, 2002). Other pro-aniogenic factors such as fibroblast growth factor (FGF), angiogenic cytokines as interleukin 8 (IL-8), tumor necrosis factoralfa (TNF-α), and transformation growth factor-beta (TGF-β) may be related to the angiogenic activity evidenced in the C. officinalis extract (Carmeliet, 2000(Carmeliet, , 2003 which is helpful for healing.…”
Section: Resultsmentioning
confidence: 99%
“…An interesting finding was observed in samples of turmeric group and marigold group at day 7 (D7), where newly formed keratinized layer of epidermis along with newly formed connective tissue was found under the scab infiltrated with reactive cells (Figure 6a, 6b). Curcumin may be useful in conditions of impaired wound healing, as it appears to induce endogenous production of TGF-β1 in the wound which can play an important role in improvement of wound repair (Mani et al, 2002). Other pro-aniogenic factors such as fibroblast growth factor (FGF), angiogenic cytokines as interleukin 8 (IL-8), tumor necrosis factoralfa (TNF-α), and transformation growth factor-beta (TGF-β) may be related to the angiogenic activity evidenced in the C. officinalis extract (Carmeliet, 2000(Carmeliet, , 2003 which is helpful for healing.…”
Section: Resultsmentioning
confidence: 99%
“…19 True to this accreditation, turmeric has been shown to be useful in the treatment of various skin diseases, inflammation, abscess, eczema, leucoderma, bruises, wounds, urticaria, psoriasis and acne. 19 Scientific studies carried out during the past three decades have shown that turmeric and its chief phytochemical curcumin possess wound-healing, [20][21][22][23][24][25][26][27][28][29][30] anti-ageing, 31,32 anti-psoriatic [33][34][35] properties and are also effective against UV-induced skin damage [36][37][38][39][40] and chemical carcinogenesis [41][42][43][44][45][46] and provide remarkable symptomatic relief for cancer patients when applied topically. 47 Clinical studies have shown that daily intake of 6 g of curcumin during the course of radiotherapy reduces the severity of radiation dermatitis in patients with breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Enhanced the formation of granulation tissue through increasing collagen and fibronectin (FN) expressions Mani et al (2002) Improved the muscle regeneration through modulating NF-κB activity Thaloor et al (1999) Suppressed the hydrogen peroxide in human fibroblasts and keratinocytes; Neutralised the activity of free radicals and inhibits cell proliferation in curcumin treated rats Gopinath et al (2004) Increased the synthesis of hexosamine, collagen, nitrite, DNA and histologic; Improved the collagen deposition and also enhances in fibroblast…”
Section: Oxidative Stress and Curcuminmentioning
confidence: 99%
“…Curcumin treatment enhanced the formation of granulation tissue through increasing collagen and fibronectin (FN) expressions that led to greater neo-vascularisation, cellular content and faster reepithelialisation through regulating the expression of nitric oxide synthase, TGF-β1, and its receptors of wound in hyperglycaemic rats (Mani et al 2002). Additionally, in an in vivo study curcumin improves the muscle regeneration through modulating the NF-κB activity during trauma (Thaloor et al 1999).…”
Section: Curcumin Enhanced Wound Healingmentioning
confidence: 99%